Studi Pustaka: Konsep Bilingualisme dan Pengaruhnya terhadap Perkembangan Bahasa Anak - Nurul Aisyah Salsabila Panjaitan; Mardiatul Husna Rambe; Rahmad Ahadi; Fauziah Nasution (Departement of Mathematics Education, 2023)
This research aims to discuss qualitative research with the literature study method. The method used is the literature study method, data collection by finding sources and constructing from various sources such as books, journals, and pre-existing research. Therefore, qualitative research is carried out with a research design whose findings are not obtained through procedures or in the form of calculating numbers, but describe holistic-contextual phenomena by collecting data from researchers and various sources and making them as instrumental keys. Qualitative research has a descriptive nature and is more likely to use inductive approach analysis, so that processes and meanings based on the subject's perspective are more prominent in this qualitative research. Based on the results of this literature study research, it can be concluded that bilingualism is a phenomenon of the use of two or more languages by a person. Bilingualism can occur due to internal as well as external factors. The internal factor for the occurrence of the phenomenon of bilingualism is the existence of intermarriage between two people which causes the offspring to have more than one language. The external factor is the presence of additional language learning as a second language. The phenomenon of bilingualism also has an impact on children's language development. Bilingualism is not a bad phenomenon for a child's language development. Children affected by the phenomenon of bilingualism tend to be considered more intelligent than monolingualism. So many educational institutions equip children with other languages even from an early age.